Toward a Bidirectional Communication Between Retinal Cells and a Prosthetic Device – A Proof of Concept - Rincón Montes, Viviana; Gehlen, Jana; Lück, Stefan; Mokwa, Wilfried; Müller, Frank; Walter, Peter; Offenhäusser, Andreas (Frontiers in Neuroscience, 2019)
Background: Significant progress towards the recovery of useful vision in blind patients with severe degenerative retinal diseases caused by photoreceptor death has been achieved with the development of visual prostheses that stimulate the retina electrically. However, currently used prostheses do not provide feedback about the retinal activity before and upon stimulation and do not adjust to changes during the remodeling processes in the retina. Both features are desirable to improve the efficiency of the electrical stimulation therapy offered by these devices. Accordingly, devices that not only enable electrical stimulation but at the same time provide information about the retinal activity are required. Given the above, a bidirectional communication strategy, in which inner retinal cells are stimulated and the output neurons of the retina, the ganglion cells, are recorded using penetrating microelectrode arrays (MEAs) is proposed. Methods: Custom-made penetrating MEAs with four silicon-based shanks, each one with three or four iridium oxide electrodes were used to record the activity of light-adapted wildtype mice retinas and degenerated retinas from rd10 mice in vitro. In addition, responses to high potassium concentration and to light stimulation in wildtype retinas were examined. Furthermore, voltage-controlled electrical stimulation was performed. Results: The spiking activity of retinal ganglion cells was recorded at different depths of penetration inside the retina. Physiological responses during an increase of the extracellular potassium concentration and phasic and tonic responses during light stimulation were captured. Moreover, pathologic rhythmic activity was recorded from degenerated retinas. Finally, electrical stimulation of the inner retina and simultaneous recording of the activity of retinal ganglion cells was accomplished. Conclusions: The access to different layers of the retina with penetrating electrodes while recording at the same time the spiking activity of retinal ganglion cells broadens the use and the field of action of multi-shank and multi-site penetrating MEAs for retinal applications. It enables a bidirectional strategy to stimulate inner retinal cells electrically and to record from the spiking retinal ganglion cells simultaneously (BiMEA). This opens the possibility of a feedback loop system to acknowledge the success of electrical stimulation carried out by retinal prostheses.